Аналіз українського політичного дискурсу - Заяць, Антоніна; Романюк, Андрій (Видавництво Львівської політехніки, 2012)
For the last decades the interest to the political language study in its different aspects has rapidly grown. All the researches in this field pursue both theoretical and practical aims.The purpose of this work is to develop a program that uses a series of dictionaries to search a passage for serten semantic features on the basis of Ukrainian political discourse.
Keywords: політичний дискурс; аналіз політичної мови; мова і політика; текстовий аналізатор; корпус політичних промов